Learnings from early production at the Kemi sublevel cave - Karlsson, M; Ihanus, J; Petäjäjärvi, A (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The sublevel caving (SLC) mine at Outokumpu’s Kemi Mine, in Finland, is in a ramp-up phase. The mine is located in the vicinity of an active underground benching mining area, both operate simultaneously in different parts of the orebody. Initial SLC design parameters were based on global benchmarking of similar mines, in-house subject-matter expertise and over 20 years of experience from underground mining of the deposit using stoping methods. Key parameters evaluated were the sublevel spacing, crosscut orientation and spacing, opening slot height, drill and blast parameters, and draw rates. Detailed life of mine (LOM) cave flow modelling and geotechnical impact assessments were conducted to support the evaluation of the parameters. This paper describes the evolution of mine design parameters from mining study phase, through trial mining, and into the current ramp-up phase. It also describes the experience gained during the early years of SLC mining and the main factors impacting successful production ramp-up are discussed.
Keywords: underground mining